Screw-in forces during instrumentation by various file systems - Jung-Hong Ha; Sang Won Kwak; Sung-Kyo Kim; Hyeon-Cheol Kim (Korean Academy of Conservative Dentistry, 2016)
Objectives The purpose of this study was to compare the maximum screw-in forces generated during the movement of various Nickel-Titanium (NiTi) file systems. Materials and Methods Forty simulated canals in resin blocks were randomly divided into 4 groups for the following instruments: Mtwo size 25/0.07 (MTW, VDW GmbH), Reciproc R25 (RPR, VDW GmbH), ProTaper Universal F2 (PTU, Dentsply Maillefer), and ProTaper Next X2 (PTN, Dentsply Maillefer, n = 10). All the artificial canals were prepared to obtain a standardized lumen by using ProTaper Universal F1. Screw-in forces were measured using a custom-made experimental device (AEndoS-k, DMJ system) during instrumentation with each NiTi file system using the designated movement. The rotation speed was set at 350 rpm with an automatic 4 mm pecking motion at a speed of 1 mm/sec. The pecking depth was increased by 1 mm for each pecking motion until the file reach the working length. Forces were recorded during file movement, and the maximum force was extracted from the data. Maximum screw-in forces were analyzed by one-way ANOVA and Tukey's post hoc comparison at a significance level of 95%. Results Reciproc and ProTaper Universal files generated the highest maximum screw-in forces among all the instruments while M-two and ProTaper Next showed the lowest (p < 0.05). Conclusions Geometrical differences rather than shaping motion and alloys may affect the screw-in force during canal instrumentation. To reduce screw-in forces, the use of NiTi files with smaller cross-sectional area for higher flexibility is recommended.